(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the agricultural sectors of the Fergana Valley, one of the most important regions of Uzbekistan, in particular agriculture, livestock breeding, sericulture and grain growing. The agricultural sector of the Fergana Valley is a unique sector that is of great importance in the economic development of the republic. In particular, the article examines the organization and general state of trade relations based on historical data.